First-line selective internal radiotherapy plus chemotherapy versus chemotherapy alone in patients with liver metastases from colorectal cancer (FOXFIRE, SIRFLOX, and FOXFIRE-Global): a combined analysis of three multicentre, randomised, phase 3 trials. Issue 9 (September 2017) - ,; ,; ,; Adams, Richard; Bateman, Andrew; Blesing, Claire; Brown, Ewan; Chau, Ian; Cummins, Sebastian; Cunningham, David; Falk, Stephen; Hadaki, Maher; et al.
Summary: Background: Data suggest selective internal radiotherapy (SIRT) in third-line or subsequent therapy for metastatic colorectal cancer has clinical benefit in patients with colorectal liver metastases with liver-dominant disease after chemotherapy. The FOXFIRE, SIRFLOX, and FOXFIRE-Global randomised studies evaluated the efficacy of combining first-line chemotherapy with SIRT using yttrium-90 resin microspheres in patients with metastatic colorectal cancer with liver metastases. The studies were designed for combined analysis of overall survival. Methods: FOXFIRE, SIRFLOX, and FOXFIRE-Global were randomised, phase 3 trials done in hospitals and specialist liver centres in 14 countries worldwide (Australia, Belgium, France, Germany, Israel, Italy, New Zealand, Portugal, South Korea, Singapore, Spain, Taiwan, the UK, and the USA). Chemotherapy-naive patients with metastatic colorectal cancer (WHO performance status 0 or 1) with liver metastases not suitable for curative resection or ablation were randomly assigned (1:1) to either oxaliplatin-based chemotherapy (FOLFOX: leucovorin, fluorouracil, and oxaliplatin) or FOLFOX plus single treatment SIRT concurrent with cycle 1 or 2 of chemotherapy. In FOXFIRE, FOLFOX chemotherapy was OxMdG (oxaliplatin modified de Gramont chemotherapy; 85 mg/m 2 oxaliplatin infusion over 2 h, L-leucovorin 175 mg or D, L-leucovorin 350 mg infusion over 2 h, and 400 mg/m 2 bolus fluorouracil followed by a 2400 mg/m 2 continuous fluorouracil infusion over 46 h). In SIRFLOX and FOXFIRE-Global, FOLFOX chemotherapy was modified FOLFOX6 (85 mg/m 2 oxaliplatin infusion over 2 h, 200 mg leucovorin, and 400 mg/m 2 bolus fluorouracil followed by a 2400 mg/m 2 continuous fluorouracil infusion over 46 h). Randomisation was done by central minimisation with four factors: presence of extrahepatic metastases, tumour involvement of the liver, planned use of a biological agent, and investigational centre. Participants and investigators were not masked to treatment. The primary endpoint was overall survival, analysed in the intention-to-treat population, using a two-stage meta-analysis of pooled individual patient data. All three trials have completed 2 years of follow-up. FOXFIRE is registered with the ISRCTN registry, number ISRCTN83867919. SIRFLOX and FOXFIRE-Global are registered with ClinicalTrials.gov, numbers NCT00724503 (SIRFLOX) and NCT01721954 (FOXFIRE-Global). Findings: Between Oct 11, 2006, and Dec 23, 2014, 549 patients were randomly assigned to FOLFOX alone and 554 patients were assigned FOLFOX plus SIRT. Median follow-up was 43·3 months (IQR 31·6–58·4). There were 411 (75%) deaths in 549 patients in the FOLFOX alone group and 433 (78%) deaths in 554 patients in the FOLFOX plus SIRT group. There was no difference in overall survival (hazard ratio [HR] 1·04, 95% CI 0·90–1·19; p=0·61). The median survival time in the FOLFOX plus SIRT group was 22·6 months (95% CI 21·0–24·5) compared with 23·3 months (21·8–24·7) in the FOLFOX alone group. In the safety population containing patients who received at least one dose of study treatment, as treated, the most common grade 3–4 adverse event was neutropenia (137 [24%] of 571 patients receiving FOLFOX alone vs 186 (37%) of 507 patients receiving FOLFOX plus SIRT). Serious adverse events of any grade occurred in 244 (43%) of 571 patients receiving FOLFOX alone and 274 (54%) of 507 patients receiving FOLFOX plus SIRT. 10 patients in the FOLFOX plus SIRT group and 11 patients in the FOLFOX alone group died due to an adverse event; eight treatment-related deaths occurred in the FOLFOX plus SIRT group and three treatment-related deaths occurred in the FOLFOX alone group. Interpretation: Addition of SIRT to first-line FOLFOX chemotherapy for patients with liver-only and liver-dominant metastatic colorectal cancer did not improve overall survival compared with that for FOLFOX alone. Therefore, early use of SIRT in combination with chemotherapy in unselected patients with metastatic colorectal cancer cannot be recommended. To further define the role of SIRT in metastatic colorectal cancer, careful patient selection and studies investigating the role of SIRT as consolidation therapy after chemotherapy are needed. Funding: Bobby Moore Fund of Cancer Research UK, Sirtex Medical.